Private Management and Public Policy: Reciprocal Impacts (Book). - Burns, Thomas J.; Cheng, Philip C. (The Accounting Review, 1981)
Abstract Reviews the book "Private Management and Public Policy: Reciprocal Impacts," edited by Lewis Benton.